Credit Cards: A Boon Or Bane For The Customers - Srivastava, D.K. (Journal of Malaysian and Comparative Law, 2019)
The last ten years have seen tremendous growth in the use of credit, debit and other similar cards. They now form an integral part of the contemporary payment system. Today an average adult Hong Konger carries 1.7 cards. Even eighteen year olds carry up to three cards. At least 50% of the people in Hong Kong carry MasterCards and Visa cards. This popularity is due largely to the many advantages that such cards offer.